Teledermatology Service During the COVID-19 Pandemic in China: A Mobile Application-Based Retrospective Study - Mu Z; Liu X; Li K; Zhang J (Dove Medical Press, 2021)
Zhanglei Mu,1 Xiaojing Liu,2 Kun Li,1 Jianzhong Zhang1 1Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of China; 2Department of Dermatology, Shanghai Skin Disease Hospital, Tongji University, Shanghai, People's Republic of ChinaCorrespondence: Jianzhong ZhangDepartment of Dermatology, Peking University People's Hospital, No. 11 Xizhimen South St, Beijing, 100044, People's Republic of ChinaTel +86-10-88325472Email rmzjz@126.comPurpose: During the COVID-19 pandemic, teledermatology service was increased rapidly. The purpose of our study was to analyze the characteristics of patients and common skin diseases via teledermatology during the COVID-19 pandemic in mainland China.Patients and Methods: During weekends between January 21 and April 4, 2020, the data of patients who used teledermatology service via a mobile application were collected, including gender, age, and diagnosis.Results: A total of 698 patients (315 men and 383 women), with a mean age of 26 years, used this service. The top ten common diseases in order of proportion were eczema (22%), acne (9%), atopic dermatitis (9%), urticaria (5%), contact dermatitis (5%), herpes zoster (3%), warts (3%), folliculitis (3%), prurigo (3%), and androgenetic alopecia (2%). When classified according to age groups, atopic dermatitis was the most common condition for patients in the first decade, acne was more prevalent in the second and third decades, and eczema was the most prevalent condition for all other age groups.Conclusion: The ten common diseases accounted for the majority of the evaluated cases and varied by age group, allowing individualizing teledermatology services.Keywords: teledermatology, COVID-19, China, clinical epidemiology, case mix, dermatology